2011
DOI: 10.1063/1.3561363
|View full text |Cite
|
Sign up to set email alerts
|

Compression behavior and phase transition of cubic In2O3 nanocrystals

Abstract: High-pressure behaviors of bixbyite-type cubic In2O3 nanocrystals with an average grain size of 6.0 nm and bulk In2O3 samples were investigated by in situ high-pressure synchrotron radiation x-ray diffraction measurements up to 40 GPa at ambient temperature. It was found that nanosized and bulk samples began to transform from cubic into hexagonal structure at about 15–25 GPa and extended up to 40 GPa. Both cubic and hexagonal phases remained after pressure release. Below the onset transition pressure, the nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
33
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 41 publications
(35 reference statements)
11
33
5
Order By: Relevance
“…[25][26][27][28][29]31 In the last years high-pressure studies of In 2 O 3 at RT have also been reported yielding some contradictory results. [32][33][34] A phase transition from c-In 2 O 3 to rh-In 2 O 3 between 12 and 25 GPa in bulk and nanocrystalline In 2 O 3 was reported, 32,33 whereas no sign of phase transition up to 30 GPa neither in bulk nor in nanocrystalline c-In 2 O 3 was found in the latest work 34 in good agreement with previous results. 28 These contradictory results at high pressure and RT have motivated us to perform a much deeper study of the polymorphism of In 2 O 3 at RT up to higher pressures (50 GPa) with both powder x-ray diffraction (XRD) and Raman scattering (RS) measurements.…”
Section: Pbcasupporting
confidence: 80%
See 2 more Smart Citations
“…[25][26][27][28][29]31 In the last years high-pressure studies of In 2 O 3 at RT have also been reported yielding some contradictory results. [32][33][34] A phase transition from c-In 2 O 3 to rh-In 2 O 3 between 12 and 25 GPa in bulk and nanocrystalline In 2 O 3 was reported, 32,33 whereas no sign of phase transition up to 30 GPa neither in bulk nor in nanocrystalline c-In 2 O 3 was found in the latest work 34 in good agreement with previous results. 28 These contradictory results at high pressure and RT have motivated us to perform a much deeper study of the polymorphism of In 2 O 3 at RT up to higher pressures (50 GPa) with both powder x-ray diffraction (XRD) and Raman scattering (RS) measurements.…”
Section: Pbcasupporting
confidence: 80%
“…We want to comment that the scheme of pressure tions here proposed for In 2 O 3 at RT is in disagreement with many previous reports results. As already commented, the observed phase transition from c with previous results which suggested that assigned by Liu et al 32 and Qi et al 33 to the R that data of the high-pressure phase reported by Liu et al and Qi et al show no XRD peak at small angles, as we have already commented we have observed for the Pbcn phase. Therefore, we think that these authors already found the phase transition from c-In 2 O 3 to o1-In 2 O 3 , even at smaller pressures than in this work likely due to the presence of slightly non hydrostatic conditions in their experiments.…”
Section: Pbcasupporting
confidence: 79%
See 1 more Smart Citation
“…In this respect, the EOS of rh-In 2 O 3 has been studied by means of theoretical calculations, 33,44,45 but the experimental determination of its bulk modulus at ambient pressure has only been estimated by extrapolation of high-pressure data to ambient pressure. 46,47 Furthermore, there is a controversy regarding the pressure range of stability of rhIn 2 O 3 . Gurlo et al showed that rh-In 2 O 3 is stable at ambient temperature between ambient pressure and 30 GPa; 37,39 however, in a recent study we have reported that rh-In 2 O 3 undergoes a transformation to o3-In 2 O 3 above 12.4 GPa at 300K.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison purposes, the EOS parameters for isostructural In 2 O 3 are also included in Table II. [41][42][43] 45 and monoclinic a-Bi 2 O 3 (S.G.: P2 1 /c, No. 14, Z ¼ 4).…”
Section: Resultsmentioning
confidence: 99%